Patients Satisfaction and Expectation Towards Different Dimensions of Health Care Service Quality of Private Hospitals - RAZEED, S. MOHAMED MOSSA HARUN; VETHIRAJAN, DR. C. (The journal of contemporary issues in business and government, 2021)
The main aim of the study is to bring out the patient satisfaction and the quality of health care service. The research has taken different dimensions of service quality namely Tangibility, Reliability, Responsiveness, Empathy and Assurance. The study is based on primary and secondary data and discussions with hospital officials including doctors, nurses and administrative staff members etc. In order to fulfill the objectives, a sample study was undertaken by using a well framed interview schedule. The respondents (Patients) were selected with various background based on important aspects of their occupation, education, age and other demographic variables from the study area i.e., Tirunelveli district. The primary data relating to the study are collected through personal interview with the patients of the private hospitals in Tirunelveli district. Personal interview by the researcher is the major tool used for the data collection. The Sample Size of the present study is 600 from 12 selected hospitals from Tirunelveli District. The primary data is gathered from the patients who are using hospital services of private Hospitals in Tirunelveli District. The data were analysed using t’ test and ANOVA. This study brought to light the fact that the patients were very much satisfied on the service quality of the private hospitals in the region but at the same time they expect a lot more from the private hospitals in the present scenario of technological developments in health care industry. Hence, this study will pave way to further research to explore this mechanism in depth to provide quality health care services to facilitate the patients, the society as a whole.